A degree of studying? Approaches to learning and academic performance among student 'consumers'. (November 2021) - Bunce, Louise; Bennett, Melanie
The marketization of higher education and focus on graduate employability and earnings data has raised questions about how students perceive their roles and responsibilities while studying for their degree. Of particular concern is the extent to which students identify themselves as consumers of their higher education, for example, whether they view their degree as a purchasable commodity to improve future earnings. This is because research has found that a stronger consumer identity is related to lower academic performance. This study examined whether this relation could be explained by the impact of a consumer identity on the extent to which students adopt deep, surface or strategic approaches to learning. The hypotheses were that the relation between consumer identity and academic performance would be mediated by approaches to learning, whereby a consumer identity would be related to adopting a more surface approach, a less deep approach and less strategic approach. Undergraduates completed an online questionnaire that assessed the extent to which they identified as a consumer, their approaches to learning and academic performance. The analysis partly supported the hypotheses: a stronger consumer identity was related to a more surface approach to learning. However, a surface approach to learning did not mediate the relation between consumer identity and academic performance. Conversely, a deep approach to learning mediated the relation between consumer identity and academic performance, whereby a stronger consumer identity was related to lower academic performance through its negative impact on a deep approach to learning. There was no relation between consumer identity and strategic approach to learning. Implications of students identifying themselves as consumers of their higher education are discussed.